Pharmacovigilance and reporting adverse drug reactions. - Isa NM (Penerbit UKM, 2014)
Drug therapy is an essential part of health care and has become a universally accepted form of medical treatment, both by health professionals and society at large. It is not an exaggeration to say that almost every human being has had an experience with drug therapy, even newborn infants are now exposed to immunisations on the day they are born. What does society want from drug therapy? Walley (1995) summarised the needs of the public as the ‘3 E’, efficacy, effectiveness and efficiency.